1973
DOI: 10.1128/aem.25.6.900-904.1973
|View full text |Cite
|
Sign up to set email alerts
|

Potential Pathogens in the Environment: Klebsiella pneumoniae, a Taxonomic and Ecological Enigma1

Abstract: A nitrogen-deficient medium and m-Endo agar were employed in the isolation of members of the tribe Klebsielleae from surfaces of vegetables and seeds. With m-Endo agar at an incubation temperature of 37 C, nearly 50% of the vegetables and seven out of seven seed samples yielded organisms which biochemically and serologically were identified as Klebsiella pneumoniae, Viable counts were generally in the range of 103 cells per g of vegetable peel or seed. Organisms classified as K. pneumoniae exhibited seven diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
34
0
1

Year Published

1978
1978
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(37 citation statements)
references
References 17 publications
2
34
0
1
Order By: Relevance
“…Other botanical materials where Kiebsiella spp. have been located include drinking-water reservoirs constructed of redwood in the western United States (Seidler, Morrow & Bagely, 1977) and the surfaces of fresh market vegetable produce (Brown & Seidler, 1973).…”
Section: Discussionmentioning
confidence: 99%
“…Other botanical materials where Kiebsiella spp. have been located include drinking-water reservoirs constructed of redwood in the western United States (Seidler, Morrow & Bagely, 1977) and the surfaces of fresh market vegetable produce (Brown & Seidler, 1973).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the bacterium is also found to colonize the mucosal layer of mammals such as the oral cavity as well as the GIT. [17][18][19] K. pneumoniae can be distinguished and classified by serotyping based on its capsule antigens. There are currently 77 serotypes belonging to the K-antigen and another 12 belonging to the O-antigen serotype.…”
Section: Epidemiology Of K Pneumoniaementioning
confidence: 99%
“…In a previous study Oger et al (1981) showed that of a total of 564 coliform strains isolated from drinking water in the course of a year, 65.8% were psychrotrophic, non-faecal coliforms. Such species have been traced to the aquatic environment (Brown et al 1973;Bagley et al 1981), encountered in food products ( Mossel et al 1979;Michard et al 1986;Hamze et al 1991) and even in clinical samples (Freney et al 1986a,b;Bollet et al 1991). These bacteria, whose natural habitat appears to be the aquatic environment, are particularly adapted to surviving in drinking water, adhering to supports, colonizing the biofilms of networks (Lechevallier et al 1987;Van der Wende et al 1990) and escaping sterilizing agents (King et al 1988;Lechevallier et al 1981Lechevallier et al , 1984.…”
Section: Discussionmentioning
confidence: 99%
“…The composition of the Enterobacteriaceae (Jones 1988) has similarly been transformed. New methods of identification have been added to the armoury because it has been shown that venerated indole/methyl red/Voges-Proskauer/Citrate (IMVIC) tests are inadequate in terms of species recognition (Ducan et al 1972;Brown et al 1973;Gavini et al 1980;Leclerc 1983). In addition to thermotrophic ('thermotolerant') coliforms of faecal origin numerous psychrotrophs have been identified (Gavini et al 1976a(Gavini et al ,b, 1977Leclerc 1983).…”
Section: Introductionmentioning
confidence: 99%